2018
DOI: 10.3390/rs10121973
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Determinants of Post-Soviet Cropland Abandonment in the Western Siberian Grain Belt

Abstract: The transition from a command to a market economy resulted in widespread cropland abandonment across the former Soviet Union during the 1990s. Spatial patterns and determinants of abandonment are comparatively well understood for European Russia, but have not yet been assessed for the vast grain belt of Western Siberia, situated in the Eurasian forest steppe. This is unfortunate, as land-use change in Western Siberia is of global significance: Fertile black earth soils and vast mires store large amounts of org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…This study developed a new approach to map abandoned cropland by monitoring the annual land-use trajectory of the study area. Comparing to the previous research [1,5,8,13,14,20,26,28,46], there are two advantages and one weakness of the developed method. First, different from most of the previous research, this research detected the abandoned cropland by monitoring the consecutive land-use conversions during a certain period.…”
Section: Positives and Weaknesses Of The Researchmentioning
confidence: 89%
See 1 more Smart Citation
“…This study developed a new approach to map abandoned cropland by monitoring the annual land-use trajectory of the study area. Comparing to the previous research [1,5,8,13,14,20,26,28,46], there are two advantages and one weakness of the developed method. First, different from most of the previous research, this research detected the abandoned cropland by monitoring the consecutive land-use conversions during a certain period.…”
Section: Positives and Weaknesses Of The Researchmentioning
confidence: 89%
“…According to previous research, the vegetation succession after land abandonment in forest vegetation areas should be subject to annual and biennial weed, perennial grass and other grass, ligneous plants, and late succession species in sequence [45]. The changes from bare land to weeds or other grasses can take one to three years, to dwarf shrubs at least five years, and to trees at least ten years without human interference [46][47][48]. Therefore, spontaneous cropland abandonment should result in weeds or grasses as the dominant vegetation grown within the first three years of abandonment.…”
Section: A Framework For Identifying Abandoned Croplandmentioning
confidence: 99%
“…Previous research has shown that the species diversity of abandoned cropland under the natural state cannot significantly be improved within a period of 5 years, making it difficult to establish forest systems on such land [3,[32][33][34]. Therefore, this study considered abandoned cropland during the 5 years from 2011 to 2016 converted into grassland and unused land, as well as abandoned cropland converted into grassland, forest land, and unused land in the next 20 years.…”
Section: Extraction Of Cra Datamentioning
confidence: 99%
“…However, this interpretation mode tends to be limited by the phenomenon of "same object but different spectra, same spectrum but different objects" [10,11,23]. Excessive dependence on the ground object spectral characteristics in remote sensing interpretation often leads to incorrect or omissive extraction [10,11,23,32]. In contrast to the traditional interpretation mode, the decision tree classification method makes full use of the remote sensing image data and other spatial data and can effectively avoid the phenomenon of "same object but different spectra, same spectrum but different objects", thereby obtaining more precise interpretation results when compared to traditional interpretation methods [10,11].…”
Section: Extraction Of Land Use Data For Wushan County In 2016mentioning
confidence: 99%
See 1 more Smart Citation